Impacts of accessibility on vertical commercial land use pattern in the central business district of Peshawar, Pakistan - Sher Muhammad Malik; Amjad Ali (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2019)
Now a days, commercial growth and development in cities are more vertical than horizontal. This vertical growth and development are controlled by the type of occupancy or land use. Higher the order of commercial activity in bid-rent system is supporting more vertical development. Consequently, the central business (CB) uses and particularly the retailing supports and control the vertical growth. Retailing and all sort of CB uses are directly associated with the mode & nature of accessibility. This study focuses on impacts of accessibility on the vertical commercial land use pattern in central business district (CBD) of Peshawar, Pakistan and thoroughly studies this association in detail. The subtypes of accessibility and retailing/commercial activity are grouped into singular expression by measures of central tendencies and then correlated with the number of visitors and level of vertical occupancy. The results show a common pattern in vertical land uses which is in liaison with the accessibility. This study not only explores the relationship of accessibility with vertical land use pattern but also provides basic information for investment and economic endeavor.
Keywords: 330; accessibility; vertical commercial land uses; central business district (CBD); commercialretailing